Development of STEM-Based Student E-Book Using PBL Model in Improving Critical Thinking Ability - Febbi Rahmadani; Yulkifli Yulkifli; Festiyed Festiyed; Asrizal Asrizal (Jurnal Penelitian Pendidikan IPA, 2025)
The ability to think critically is an ability needed by students in the 21st century. Problem-based learning is one of the learning models that can stimulate students' critical thinking skills. Students' difficulties in solving contextual problems of temperature and heat material oriented to students' critical thinking skills and the unavailability of teaching materials that facilitate students in improving students' critical thinking skills. This study used Research & Development with Plomp's development model. The research subjects were 36 students of class XI in each high school in Solok City. Research data in the form of needs analysis (curriculum analysis, material, learner character analysis) development analysis (product design, formative evaluation) and assessment analysis (normality test, homogeneity, critical thinking ability hypothesis). The results showed that student e-books were in the valid category while in terms of material experts were in the valid category and the practicality of student e-books was seen in the results of student responses with an average of 93% with a very practical category and the effectiveness of student e-books seen in the average N-gain value of 0.683. The resulting student e-book is feasible to be used by teachers in the learning process, problem-based learning models will be more effective in spurring critical thinking skills if teachers use this student e-book.